KEAMANAN OBAT TRADISIONAL JAMU KUNYIT ASEM DI BEBERAPA PASAR TRADISIONAL KOTA MALANG - sandry kesuma (LPPM Akafarma Sunan Giri Ponorogo, 2021)
Traditional medicine (herbal medicine) including traditional drinks that are still consumed by the community, so it must be considered the safety of traditional medicine both in terms of microbes and their chemical aspects. Based from BPOM RI rules No. 12 2014 concerning requirements for traditional medicines may not contain Escherichia coli with negative/ml or <3MPN/ml and BPOM RI rules No. 32 2019 concerning safety and quality requirements of traditional medicines with a cyclamate use limit of 1,250g g/L. The research uses the MPN method, gram staining and gravimetric aim to determine Escherichia coli contamination and cyclamate content in tamarind turmeric herbs in several traditional markets in Malang. The research is a descriptive research with observational design. The number of samples are 4 tamarind turmeric herbs from Bareng market, Besar market, Sukun market and Oro-orodowo market. The result of Escherichia coli test showed that 1 positive sample contained Escherichia coli with an MPN value of 7,4 MPN/ml and 1 positive sample contained cyclamate with levels of 4,0182 g/L that didn’t meet the requirements